Membincang Pembubaran Front Pembela Islam dalam Framing Pemberitaan Republika.co.id - Fiiki Ridho Rabbina; Ali Irfani (Jurnal Studi Jurnalistik, 2022)
The Indonesian government's decision to dissolve the Front Pembela Islam (FPI) has sparked controversy. Republika.co.id is one of the online media that intensively reported on the disbandment of FPI three days after the government's decision was delivered, which was to release 47 stories on its online site. This article aims to find out how the Republika.co.id media framed the issue concerning the history of Republika as a media that was created by the Indonesian Muslim Intellectuals Association (ICMI), one of the famous Islamic groups in Indonesia. In addition, this article also analyzes how media framing is related to media ownership to see the media's alignment with power. This article uses framing analysis by Zhongdang Pan and Gerald M. Kosicki to determine how the text strategy of media builds frames. The results show that the Republika.co.id remains critical of the government's policy of disbanding FPI as an organization even though the media owners are part of the government.